Organizing Organizational Studies in Chile: History of the Creation of the Minga Group - Perez-Arrau, J (Fundacao Getulio Vargas, 2020)
This article addresses the experience, history, and particularities after the process of shaping Minga, an academic group of Organizational Studies in Chile. Following a historical-narrative methodology, a biographical account of this group is built, in which its protagonists participate as researchers and authors of the process. To analyze this story, a decolonial view is adopted, simultaneously investigating the leadership styles and the knowledge network that this experience mobilizes, paralleling the tradition of the minga chilota. The results show how the question for organizational studies in Chile coincides with a process of epistemic detachment from the global north, through which the collective and shared leadership among its members is consolidated in Minga, as well as its functioning as an inter-organizational academic network. The conclusions cover some of the learnings that the history and conformation of this group offer for other groups with similar intentions in the field of Organizational Studies in Latin America. © RAE.